Effectiveness of Short Term Percutaneous Tibial Nerve Stimulation for Non-neurogenic Overactive Bladder Syndrome in Adults: A Meta-analysis - Elita Wibisono; Harrina E Rahardjo (Interna Publishing, 2015)
Aim: to evaluate the effectiveness of short-term PTNS for non-neurogenic OAB in adults systematically by comparing with sham procedure and other treatments. Methods: we performed a systematic review of cohort study. Data sources were MEDLINE, EMBASE, CINAHL, National Library for Health, Cochrane, and google scholar from 2005 through 2015. Meta-analysis was performed using the random effects model. Heterogeneity of effects was assessed by calculating I2 statistic. Statistical analysis was performed using Review Manager 5.3 for RCT meta-analysis. Results: we analized 11 randomised controlled trial (RCT) and five prospective non-comparative studies with variable success rate. Based on percentage of responders, the results were 37.3% - 81.8% in PTNS group, 0% - 20.9% in sham group, 54.8% in anti-muscarinic group, and 89.7% in multimodal group. The decrease of voiding symptoms episodes per day was found in PTNS (0.7-4.5), sham (0.3-1.5), and anti-muscarinic (0.6-2.9) groups. In meta-analysis of four RCTs, the results favour PTNS over sham procedure with overall risk ratio of 7.32(95% CI of 1.69-32.16), p=0.09, I2=54%. Conclusion: there is an evidence of effectiveness of short term PTNS in treatment of non-neurogenic OAB. PTNS is proven significantly better than sham procedure. Key words: overactive bladder, percutaneous tibial nerve stimulation, sham, anti-muscarinic, voiding symptoms.